Role of Goghrta (Cow’s Ghee) and Medicated Ghrta (Medicated Ghee) In Metabolism and Managing Metabolic Disorders (AYUSHDHARA, 2023)
Metabolism is a complex process involving all the chemical reactions in the body to maintain life and is controlled by various hormones and enzymes. Carbohydrate, lipid and protein metabolism are the processes by which the body converts nutrients into energy and other essential molecules. According to Ayurveda, the overall metabolism of the body depends upon proper functioning of Agni and improper dietary habits cause deranged functioning of Agni leading to various metabolic disorders. Maintaining a strong Agni, balancing the Doshas, nourishing the Dhathu through a healthy diet is a key way to optimize metabolism. Goghrta (Cow’s ghee) has been given foremost importance and has been an inevitable part of diet in the Indian cuisine. Ayurveda considers Goghrta as the best among all fats. Ghrta can act on various levels of metabolism correcting the functions of Agni, Doshas and Dhathus. When digestion becomes normal Poshaka dhathu is formed from excellent Ahara rasa which enhances Bala, Varna, Ojas etc. The Rasayana effect of Ghrta helps to maintain the quality of Dhathus formed thereby promote health and longevity by improving metabolism and provides a healthy body. So it is good to include Goghrta in our daily diet in small quantities but large quantity may cause difficulty in digestion leading to Ama formation. Due to the Samskarasya Anuvarthana and Yogavahi property, medicated Ghrta makes it wider application in different diseased conditions. This review is to highlight the potential health benefits of Goghrta in metabolism and the role of medicated Ghrta in managing metabolic disorders.